Implementasi Corak ‘Adabul Ijtima’i Dalam Tafsir Qur’an Karim Karya Mahmud Yunus - Wicaksana, Mujahidin Amhar; Sartika, Ela; Setiadi, Andri (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
This research is motivated by the emergence of tafsir in the 20th century using different nuances from previous writing. The writing of Indonesian tafsir will be very strong with socio-cultural influences and various traditions which are the specialty of tafsir itself, including Tafsir Qur'an Karim by Mahmud Yunus which was born in the 20th century. This research aims to identify aspects of the socio-cultural approach (adabul ijtima' i) in the interpretation of Mahmud Yunus in his interpretation. Meanwhile, the research method used in this research uses a qualitative method with a library research approach. So the results of this research include, firstly, Mahmud Yunus is known as a productive mufassir both in educational circles and mufassir circles. Second, writing tafsir as a medium for da'wah in simple language causes this tafsir to be well received among the public. Third, the influence of social culture, locality and traditions in Indonesia shows that Mahmud Yunus used this approach in his interpretation to give the impression that the Al-Qur'an is easy to understand and can be used as a guide in life.